The effect of different pyrolysis temperatures on the speciation and availability in soil of P in biochar produced from the solid fraction of manure. (February 2017) - Bruun, Sander; Harmer, Sarah L.; Bekiaris, Georgios; Christel, Wibke; Zuin, Lucia; Hu, Yongfeng; Jensen, Lars Stoumann; Lombi, Enzo
Abstract: Biochar application to agricultural land has been proposed as a means for improving phosphorus (P) availability in soil. The purpose of the current study was to understand how pyrolysis temperature affects P speciation in biochar and how this affects availability of P in the amended soil. Biochar was produced at different temperatures from digestate solids. The primary species of P in digestate solids were simple calcium phosphates. However, a high co-occurrence of magnesium (Mg) and P, indicated that struvite or other magnesium phosphates may also be important species. At low temperatures, pyrolysis had little effect on P speciation; however, as the temperature increased above 600 °C, the P gradually became more thermodynamically stable in species such as apatite. At very high temperatures above 1000 °C, there were indications of reduced forms of P. Biochar production decreased the immediate availability of P in comparison with the original digestate solids. However, for biochar produced at low temperatures, availability quickly increased to the same levels as in the digestate solids. For biochar produced at higher temperatures, availability remained depressed for much longer. The low availability of P in the biochar produced at high temperatures can probably be explained by the formation of less soluble P species in the biochar. In contrast, the transient decrease of availability of the P in the biochar produced at low temperatures can be explained by mechanisms, such as sorption on biochar, which gradually decreases because of oxidation of the biochar surfaces or changes in pH around the biochar particles. Graphical abstract: Highlights: Pyrolysis temperatures above 600 °C result in gradually less soluble P species. Biochar has lower immediate P availability in soil compared to the feedstock. For most biochars P availability in soil increases with time after application. Only exception are high temperature biochar in pH neural and high clay soil.